THE EFFECTIVENESS OF MIND MAPPING AND PICTURES SERIES IN ENHANCING TENTH-GRADE STUDENTS’ DESCRIPTIVE WRITING SKILLS AT SULTAN FATTAH DEMAK VOCATIONAL SCHOOL - Dewi Noviyanti; Suwandi; Senowarsito (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Writing is one of the essential skills in learning English; however, many students face challenges in organizing ideas coherently, using correct grammar, and maintaining motivation to write. These difficulties often arise from the lack of engaging and relevant teaching strategies. In response to this issue, this study aims to examine the effectiveness of visual-based techniques, namely mind mapping and picture series, in enhancing students' descriptive text writing skills. This research adopted a quasi-experimental design with a non-equivalent control group. Two groups of students—experimental and control—participated in the study. The experimental group was taught using visual techniques (mind mapping and picture series), while the control group followed conventional methods. Pre-tests and post-tests were conducted to evaluate the students' writing performance before and after the intervention. The findings revealed that the experimental group showed a significant improvement in descriptive writing skills compared to the control group. Specifically, mind mapping helped students systematically organize their ideas, while picture series provided visual stimuli that enhanced creativity and engagement. Statistical analysis demonstrated that both techniques effectively addressed students' writing challenges and boosted their motivation. The study concludes that visual-based teaching techniques are beneficial in improving students' ability to produce well-structured, coherent, and engaging descriptive texts.